Program One Day Boarding School Di Sekolah Muhammadiyah Dilihat Dari Prestasi Siswa: Program One Day Boarding School di Sekolah Muhammadiyah dilihat dari Prestasi Siswa - Fudlo, Nanik (Universitas Muhammadiyah Sidoarjo, 2020)
This modern era of Islamic educational institutions in Indonesia at least begins with the Muhammadiyah movement as a public school plus and loving the Qur'an. In addi- tion to developing schools as